1996
DOI: 10.1016/0014-5793(96)00819-8
|View full text |Cite
|
Sign up to set email alerts
|

An actin point‐mutation neighboring the ‘hydrophobic plug’ causes defects in the maintenance of cell polaroty and septum organization in the fission yeast Schizosaccharomyces pombe

Abstract: The fission yeast cps8 mutation gives rise to abnormally enlarged and dispolarized cells, each of which contains several nuclei with aberrant multisepta. Molecular cloning and sequence analysis of the cps8 gene indicated that it encodes an actin with an amino acid substitution of aspartic acid for glycine at residue 273 in the hydrophobic loop that is located between actin subdomains 3 and 4. Fluorescence microscopy using phalloidin and anti-actin antibody revealed changes in the F-actin structure and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 34 publications
4
54
0
1
Order By: Relevance
“…To examine the delay in anaphase A onset more accurately, we monitored centromere dynamics in the actin mutant cps8-188 and in cdc11-123 cells, in which astral microtubule attachment to the spindle pole and spindle rotation are compromised (Ishiguro and Kobayashi, 1996;Krapp et al, 2001;Gachet et al, 2004). Single cell analysis revealed that cps8-118 ndc80-gfp cells remained in prometaphase and metaphase for 20 Ϯ 3 min ( Figure 7A), longer than in wild-type cells at the same temperature, but similar to that observed in wildtype cells in the presence of 1.25 M latrunculin A (Figure 2), consistent with our previous observations (Gachet et al, 2004).…”
Section: The Soc Is Activated By Disruption Of Astral Microtubule Conmentioning
confidence: 99%
“…To examine the delay in anaphase A onset more accurately, we monitored centromere dynamics in the actin mutant cps8-188 and in cdc11-123 cells, in which astral microtubule attachment to the spindle pole and spindle rotation are compromised (Ishiguro and Kobayashi, 1996;Krapp et al, 2001;Gachet et al, 2004). Single cell analysis revealed that cps8-118 ndc80-gfp cells remained in prometaphase and metaphase for 20 Ϯ 3 min ( Figure 7A), longer than in wild-type cells at the same temperature, but similar to that observed in wildtype cells in the presence of 1.25 M latrunculin A (Figure 2), consistent with our previous observations (Gachet et al, 2004).…”
Section: The Soc Is Activated By Disruption Of Astral Microtubule Conmentioning
confidence: 99%
“…The ring is made of actin, one or possibly two myosins (Myo2p and Myp2), a tropomyosin (Cdc8p), and presumably two light chains, one of which is Cdc4p (5,9,12,13,23,28,32). Although intact myosin has yet to be purified from S. pombe, there is genetic, biochemical, and structural evidence in favor of a role for Cdc4p as a myosin essential light chain (9,11).…”
Section: Is the Sole Function Of Cdc4p That Of A Myosin Essentialmentioning
confidence: 99%
“…The F-actin patches localize to both growing ends of the cylindrical cell during interphase. It is suggested that the F-actin patches play a role in polarized cell growth (Kobori et al, 1989;Ishiguro and Kobayashi, 1996). The localization of F-actin patches has been shown to be controlled by small GTPbinding proteins and various actin-modulating proteins (for review see Gould and Simanis, 1997;Ishiguro, 1998;Le Goff et al, 1999).…”
Section: Assembly Of the Contractile Ring Introductionmentioning
confidence: 99%